Diagnostic and Treatment of Spinal Fracture and Luxation in Italian Wolves (Canis lupus italicus) - Domenico Fugazzotto; Chiara Costa Devoti; Maria Pia Dumas; Chiara Teani; Elisa Berti; Offer Zeira (Animals, 2022)
The medical records of 14 Italian wolves (Canis lupus italicus) with a vertebral fracture or luxation (SFL) between C1 and L7 treated at Ospedale Veterinario San Michele from 2017 and 2022 were reviewed. The most common cause of SFL was “road traffic accident”. Neurological signs were graded from 0 to 6 using a modified Frankel scale. Spinal fractures occurred in C1–C5 in 1 case, in T3–L3 in 11 cases and in L4–L7 in 2 cases. Six wolves were euthanized without treatment because they presented paraplegia without deep pain perception (DPP). Two animals with motor function were treated conservatively, and later on one of them was euthanized because of neurological impairment. Six wolves were surgically treated. Seven wolves had good neurological recovery, and six of them were released into the wild. Our results suggest that wolves with DPP before surgery may have a good functional recovery.